2004
DOI: 10.1007/s11082-004-2040-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high speed all-optical shift registers and their applications in OTDM networks

Abstract: All-optical shift registers are basic building modules for the development of ultra-high speed optical time division multiplexing networks. In this paper, we review the progress that has been made in this cutting-edge technology, focusing on implementations that exploit the attractive features of semiconductor optical amplifier (SOA)-based interferometric configurations. We present regenerative storage performed with an all-optical recirculating shift register with an inverter at 10 Gb/s using a SOA-assisted S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 84 publications
0
40
0
3
Order By: Relevance
“…Unsaturated small amplifier gain (G ss ) of SOA is related with injection current (I ) and carrier lifetime (τ e ) by the formula [27]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsaturated small amplifier gain (G ss ) of SOA is related with injection current (I ) and carrier lifetime (τ e ) by the formula [27]:…”
Section: Resultsmentioning
confidence: 99%
“…Application of TOAD in ultrafast all-optical switching has received a great deal of interest in the last few years because of its simplicity and low switching energy [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Sokoloff et al demonstrated a new device, the terahertz optical asymmetric demultiplexer (TOAD) capable of demultiplexing data at 50 Gbits/s [4].…”
Section: Principle and Operation Of Toad-based Optical Switchmentioning
confidence: 99%
“…It thus received wide application, including in simulation of noise in signal transmission, data encryption/decryption, and in bit error rate testers (BERT) [34]. The recent achievements in photonics signal processing spurred more interest towards realizing high speed all-optical PRBS generation.…”
Section: All-optical Encryption and Decryption Using Qd-soamentioning
confidence: 99%
“…In particular the AND gate is indispensable for achieving this goal as it is involved in the accomplishment of numerous tasks in the optical domain both in fundamental and system-oriented level, such as buffering [2], address comparison [3], add-drop multiplexing [4], packet clock and data recovery [5], packet header and payload separation [6], binary pattern recognition [7], binary counting [8], analog-to-digital conversion [9], digital encoding and comparison [10], data regeneration [11], waveform sampling [12], half addition [13], multiplication [14], construction of other logic gates [15] and of combinational logic circuits [16]. Given its important, multi-lateral role the AND gate has attracted intense research interest and among the technological options that exist for its implementation those that exploit a semiconductor optical amplifier (SOA) are well established [17].…”
Section: Introductionmentioning
confidence: 99%